Hematological parameters vary with life history stage in the pale-breasted thrush Turdus leucomelas - Provinciato, Ivan Celso C. [UNESP]; Ouyang, Jenny Q.; Cruz-Neto, Ariovaldo P. [UNESP] (My University, 2024)
The avian life cycle is composed by a progressive sequence of life history stages (LHS). Changes in energy expenditure and exposure to stressors at different LHS require corresponding changes in behavior, physiology, and morphology. Variation in hematological parameters, such hematocrit (Hct), hemoglobin (Hb), and heterophil to lymphocyte ratio (H/L ratio), can have permissive, stimulatory, and preparative actions to help maintain homeostasis through different LHS. Few studies have examined differences in these parameters among different LHS in free-living birds, with most of them restricted to temperate zones. We collected blood samples and measured hematological parameters every week for over a year from a population of a common resident bird species in southeastern Brazil, the pale-breasted thrush Turdus leucomelas. Hematocrit and hemoglobin concentration were highest during the onset of the reproduction and lowest during molt. Furthermore, H/L ratios were higher at the end of the reproduction, indicating that the breeding season could be the most stressful period of the year for this population of thrushes. There was no difference between sexes for any hematological parameter at any LHS. These results show that there is a permissive physiological effect for Hct and Hb to facilitate LHS transitions and that reproduction could be the most stressful event for this species. Lastly, these results mirror those from temperate species despite distinct environmental differences between these regions.
Keywords: annual cycle; H/L ratio; hematocrit; hemoglobin; thrush; Turdus leucomelas